Emergence of infections with Schistosoma mansoni in the Dhofar Governorate, Oman - Idris, Mohamed; Shaban, Mahmoud; Richter, Joachim; Moné, Hélène; Mouahid, Gabriel; Ruppel, Andreas (Acta tropica, 2003)
Infections with Schistosoma mansoni were identified in an area of Dhofar (Oman), where this parasite had been virtually absent during recent years and was reported only very sporadically before 1992. In the present survey, performed late in 2001, between 1 and 13% of children (n=519) were found to excrete eggs (one Kato-Katz-smear) in four schools, from four different villages, but no infections were detected in additional five schools (n=281). Infections were light (<72 eggs/g of faeces) in 19 of the 36 children found infected. Serologic examination of sera (n=511) was done by ELISA (based on soluble worm antigen) and immunofluorescence tests (IFT, based on cryostat sections of adult S. mansoni). The prevalence according to serological tests was between 3 and 43% in the four schools with infected children. Positive test results were taken to reflect active infections, since false positive reactions could largely be excluded. According to ultrasound (US) examinations performed on 96 individuals (children and adults) from the four villages, livers were normal in all except three cases of mild pathology, which could be assigned to schistosomiasis mansoni (pattern C, ages 32-40 years). All data suggest that transmission of S. mansoni has been re-introduced only recently in Dhofar and that this emergence of schistosomiasis is limited to at most a few foci.
Gesehen am 14.04.2021